Morphological redescription of the immature and adult stages of Culex (Culex) acharistus Root (Diptera: Culicidae) - Laurito, Magdalena; Almirón, Walter Ricardo; Rossi, Gustavo Carlos (Zootaxa, 2009)
Culex (Culex) acharistus Root is redescribed in the adult, pupal and larval stages. The male genitalia, pupa, and fourthinstar larvae are illustrated. The paper includes available information on the distribution, bionomics and taxonomy of the species.